Exploring the Interrelationship between Career Identity and English Learning for Chinese University Graduates: Narrative Cases - , Pu Wang (Archives of Current Research International, 2016)
This article aims to explore how Chinese University graduates’ career identity is interrelated with their English language learning through semi-structured narrative interview of 2 Chinese university graduates. Based on the interview, the analysis focuses on Chinese students’ self-assessment concerning the interplay of their career identity and English learning, which is influenced by their family background, career dream and major choice, English learning approaches, work/internship with English. For Chinese university graduates, career identity and English learning experience correlate with each other in constructing the career path in the future.